Efeitos da injeção de moxonidina no controle da ingestão de sódio e regulação cardiovascular - Oliveira, Lisandra Brandino de (2003)
Deficit of water and sodium in the body is detected by receptors located in different parts of the body. These receptors or hormones signalize to specific areas in the brain that control renal responses and water and sodium intake. Among these areas are: organum vasculosum of the lamina terminalis (OVLT), subfornical organ (SFO), anteroventral third ventricle (AV3V) region, hypothalamus, amygdala, septal area (SA), nucleus of the solitary tract (NTS), area postrema (AP) and lateral parabrachial nucleus (LPBN). Besides the regulation of fluid and electrolytic balance, these areas are also involved in cardiovascular control. Angiotensin II (ANG II) is a peptide that induces water and sodium ingestion and participates in cardiovascular regulation. Other neurotransmitters, like serotonin, cholecystokinin and atrial natriuretic peptide, can inhibit water and sodium intake. Another important inhibitory mechanism for water and sodium intake is related to central α2-adrenergic/imidazoline receptors. Central injection of the anti-hypertensive drugs, moxonidine and clonidine (α2-adrenergic/imidazoline receptor agonists), reduces water and sodium intake in different protocols (water dehydration, 24 h sodium depletion and administration of ANG II). So, the goals of this study were: a) to study the effects of moxonidine injected into the cerebral ventricles (lateral ventricle - LV and 4th ventricle - 4th V), amygdaloid complex, central nucleus of amygdala (CNA), basal nucleus of amygdala (BNA) and lateral hypothalamus (LH) on 0.3 M NaCl intake induced by sodium depletion (treatment combining subcutaneous injection of furosemide + sodium deficient food for 24 h); b) to test the effects of moxonidine injected into LV, 4th V and LH on the pressor response produced by the injection of ANG II and carbachol (cholinergic agonist) into the LV; c) to investigate the participation of α2-adrenergic receptors on the effects of moxonidine, injected into LV, on sodium depletion-induced 0.3 M NaCl intake and ANG II-induced pressor response; d) using imunohistochemical technique, to detect c-fos protein in forebrain areas after moxonidine injection into LV in normovolemic rats, sodium depleted rats or rats that were treated with central injection of ANG II. Male Holtzman rats with a stainless steel guide-cannulas implanted into the cerebral ventricles: LV (volume of injection: 1-3 µl) and 4th V (volume of injection: 1 µl); unilaterally into LH (volume of injection: 0.5 µl) and bilaterally into the amygdaloid complex (volume of injection: 1 µl), CNA (volume of injection: 0.2-0.4 µl) and BNA (volume of injection: 0.2-0.4 µl) were used. Moxonidine (20 nmol) injected into LV reduced sodium depletion-induced 0.3 M NaCl intake during all the period of the experiment (120 min), while moxonidine injected into 4th V, reduced 0.3 M NaCl intake only in the first 60 min. Bilateral injections of moxonidine (5, 10 and 20 nmol/1 µl) into amygdaloid complex and BNA (20 nmol/0.4 µl), but not into CNA, reduced sodium depletion-induced 0.3 M NaCl intake. Unilateral injection of moxonidine into LH did not change sodium depletion-induced 0.3 M NaCl intake. These results show that the activation of α2-adrenergic/imidazoline receptors produced by the injection of moxonidine into LV, 4th V and amygdaloid complex (especially into the BNA), but not into LH and CNA, reduce hypertonic NaCl intake. To investigate the role of the α2-adrenergic receptors on the inhibitory effect of moxonidine on 0.3 M NaCl intake, specific α2-adrenergic receptor antagonists, such as RX 821002, yohimbine and SKF 86466, were combined with moxonidine. The results show that icv injection of RX 821002 (40 and 80 nmol) and SKF 86466 (640 nmol) abolished the inhibitory effect of moxonidine (20 nmol) on 0.3 M NaCl intake during all the period of the experiment, while yohimbine (320 nmol) abolished the antinatriorexigenic effect of moxonidine only in the last hour of the experiment (60 to 120 min). These results suggest the involvement of central α2-adrenergic receptors on the inhibitory effect of moxonidine on sodium depletion-induced 0.3 M NaCl intake. Besides, we observed an increase on sodium depletion-induced 0.3 M NaCl intake following the treatment with RX 821002 (40 nmol) and yohimbine (320 nmol) alone, that suggests a possible tonic function to the central α2-adrenergic receptors on the control of hypertonic NaCl intake. The injection of moxonidine alone (respectively, 20 and 80 nmol) into LH and VL did not change mean arterial pressure (MAP) and heart rate (HR), while moxonidine administered into 4th V produced hypotension and bradycardia. The 80 nmol dose of moxonidine injected into LV reduced the pressor response produced by central injections of ANG II (50 ng) and carbachol (4 nmol). Moxonidine (20 nmol) injected into LH and 4th V reduced the ANG II-induced pressor response, but not carbachol-induced pressor response. So, it was demonstrated that central injection of moxonidine reduces the pressor responses produced by angiotensinergic (mainly) and cholinergic activation (in a minor degree). The injection of yohimbine (320 nmol) into the LV abolished the inhibitory effect of moxonidine (80 nmol), also injected into LV, on the pressor response produced by icv injection of ANG II, suggesting that moxonidine acting through central α2-adrenergic receptors inhibits ANG IIinduced pressor response. The injection of moxonidine into LV in normovolemic and satiated rats induced the expression of c-fos protein in the following areas: OVLT, ipslateral lateral septal area (ipsLSA), ventral median preoptic nucleus (vMPN), paraventrivular nucleus (PVN) and supraoptic nucleus (SON). These areas are involved in the fluid and electrolytic balance and cardiovascular regulation. ANG II injected into LV produced c-fos expression in the following areas: ipsLSA, dorsal median preoptic nucleus (dMPN), PVN and SHN and reduced cfos expression in contLSA (contra lateral lateral septal area). Previous injection of moxonidine did not change the c-fos protein expression induced by central injection of ANG II. Separated treatments with moxonidine and ANG II produce c-fos expression in similar areas, so it is difficult to know which treatment is responsible to c-fos protein expression observed after the combination of the two treatments. Maybe, moxonidine could be inhibiting the c-fos expression induced by ANG II and the c-fos expression noted after the combined treatment could be produced only by moxonidine. In sodium depleted rats, icv injection of moxonidine induced an increase on c-fos expression in ipsLSA and dMPN, and a decrease in OVLT, suggesting that changes in the activity of these areas could be responsible to the inhibitory effect of moxonidine on 0.3 M NaCl intake. In summary, the results showed: a) moxonidine injected into LV, 4th V, amygdaloid complex and BNA, but not into LH and CNA, inhibits sodium depletion-induced 0.3 M NaCl intake; b) RX 821002, yohimbine and SKF 86466 (specific α2-adrenergic receptor antagonists) abolished the inhibitory effect of moxonidine on 0.3 M NaCl intake, suggesting that the inhibitory effect of moxonidine is mediated through α2-adrenergic receptors. RX 821002 and yohimbine increased sodium depletioninduced 0.3 M NaCl intake, suggesting a possible tonic role of α2-adrenergic receptors on the inhibition of NaCl intake; c) moxonidine injected into LV, 4th V and LH reduced the pressor response produced by central angiotensinergic activation, while moxonidine injected only into LV was able to reduce the pressor effect of carbachol. Therefore central injection of moxonidine can inhibit mainly the ANG II-induced pressor response and only partially carbachol-induced pressor response. The reduction on ANG II-induced pressor response produced by moxonidine injected into LV was abolished by the pre treatment with yohimbine, suggesting the involvement of central α2-adrenergic receptors on the inhibitory effect of moxonidine on the pressor response produced by angiotensinergic activation; d) in normovolemic and satiated rats, moxonidine injected into LV induced c-fos expression in several cerebral areas: OVLT, ipsLSA, vMPN, PVN and SON. ANG II (50 ng) injected into LV increased c-fos expression in the following areas: ipsLSA, dMPN, PVN and SHN and reduced c-fos expression in contLSA. The icv injection of moxonidine did not change de c-fos expression induced by ANG II. e) in sodium depleted animals, the icv injection of moxonidine induced an increase in c-fos expression in ipsLSA and dMPN and a reduction in OVLT, suggesting that changes in the activity of these areas could be responsible to the inhibitory effect of moxonidine on 0.3 M NaCl intake in this protocol.